Foreign body aspiration in children [Cocuklarda yabanci cisim aspirasyonu.] - (:unkn) unknown (My University, 2004)
OBJECTIVES: The aim of this study was to present the demographic data of our patients who underwent bronchoscopy for suspected aspiration of a foreign body. We also assessed the sensitivity and specificity of history, symptoms, physical examination, and radiological findings in these patients. PATIENTS AND METHODS: One-hundred and two patients underwent bronchoscopy for suspected foreign body aspiration during a 23-month period. Bronchoscopy was performed under general anesthesia with a rigid bronchoscope. RESULTS: A foreign body was detected in 78 patients. The male-to-female ratio was 1.7:1, the mean age was 30.4 months, and the median age was 18 months. Nut and sunflower seeds were the most common types of foreign bodies. There were three minor complications and no death in our series. No tracheotomy or thoracotomy were required. The sensitivity and specificity of history, symptoms, physical examination, and radiological findings for suspected foreign body aspiration were 100% and 4.2%, 97.4% and 8.4%, 89.7% and 37.5%, 76.8% and 50%, respectively. CONCLUSION: A chocking crisis is an absolute indication for bronchoscopy. Our low complication rate allowed us to perform bronchoscopy more liberally in patients with suspected foreign body aspiration. The sensitivity of history, symptoms, and physical findings were very high, whereas the specificity of history and symptoms were very low.